Pengaruh Rasio Likuiditas, Rasio Biaya, Kecukupan Modal, dan Risiko Kredit sebagai Moderasi terhadap Profitabilitas Bank - Kurniawan, Camilla Casimira; Irawan, Judith Felicia Pattiwael (E-Jurnal Akuntansi; Vol 31 No 12 (2021)DO - 10.24843/EJA.2021.v31.i12.p11, 2021)
The 2020 pandemic affected the economic sector, including banking sector, especially banks in the BUKU 1 category. This study aims to identify internal factors that affect bank profitability between normal conditions in 2019 and conditions when economic growth experienced a contraction due to the pandemic in 2020. This study is based on the theory of Asset-Liability Management (ALM) and uses multiple linear regression method with ROA as a measure of profitability, LDR, BOPO, and CAR as independent variables, and NPL as quasi moderator. The results of this study provide findings that to maintain profitability, banks need to pay attention to cost efficiency which is reinforced by the risk of bad loans. Meanwhile, in unstable conditions, there are additional liquidity risk factor that must also receive attention. Thus, the results of this study are in line with the liability management approach. Keywords : Bank profitability; Normal Condition, Contraction of Economic Growth.